2021
DOI: 10.1101/2021.03.07.21253072
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persistence of symptoms up to 10 months following acute COVID-19 illness

Abstract: Importance: COVID-19 symptoms are increasingly recognized to persist among a subset of individual following acute infection, but features associated with this persistence are not well-understood. Objective: We aimed to identify individual features that predicted persistence of symptoms over at least 2 months at the time of survey completion. Design: Non-probability internet survey. Participants were asked to identify features of acute illness as well as persistence of symptoms at time of study completion. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 7 publications
1
21
0
3
Order By: Relevance
“…37,45,50,52 Additionally, two studies found older age to be associated with PASC. 20,58 Other risk factors for PASC including number of symptoms during acute COVID-19, 16 fatigue 18 , dyspnea, 18,39 muscle pain, 50 headache, 18,20 myalgia, 18 and pre-existing conditions such as obesity, 18,52 comorbidity, 45 and hypothyroidism 37 were found positively associated with PASC (eTable 4).…”
Section: Pasc Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…37,45,50,52 Additionally, two studies found older age to be associated with PASC. 20,58 Other risk factors for PASC including number of symptoms during acute COVID-19, 16 fatigue 18 , dyspnea, 18,39 muscle pain, 50 headache, 18,20 myalgia, 18 and pre-existing conditions such as obesity, 18,52 comorbidity, 45 and hypothyroidism 37 were found positively associated with PASC (eTable 4).…”
Section: Pasc Risk Factorsmentioning
confidence: 99%
“…19 Existing research suggests older age to be associated with a moderate increased risk of persisting symptoms (for ten-year increments past age of 40, estimated odds ratio (OR) is 1.10 [95% CI: 1.01-1.19]). 20 Moreover, the existing inequities by race/ethnicity as it pertains to PASC remain largely unexplored, 21 despite the same having been shown for COVID-19. Select comorbidities have been identified as being associated with PASC in the existent literature (e.g., increased risk of PASC among individuals with asthma, 18 though these findings are generally in early stages).…”
Section: Introductionmentioning
confidence: 99%
“…The idea that SARS-CoV-2 infection could be associated with long-term health outcomes first appeared in the literature in mid-2020 [11], along with previous evidence of longhaul symptoms following the Ebola [12] virus outbreak and infections from previous coronaviruses [13,14]. COVID-19 survivors have been shown to experience a constellation of symptoms such as fatigue, dyspnea or breathlessness [8,15], palpitations [16,17], brain fog, lack of concentration [18,19], sleep disturbances (i.e., insomnia) [20], headache [17,[21][22][23][24][25], orthostatic intolerance [25], anxiety and post-traumatic stress disorder [20,23,[26][27][28], chest pain, joint pain [8], sore throat [17], and hair loss [15] persisting >4 weeks after recovery. These clinical sequelae share similarities with post-acute symptoms reported after severe acute respiratory syndrome (SARS) and Middle East Respiratory Syndrome (MERS) epidemics, caused by previous coronaviruses [14].…”
Section: Post-acute Sequelae Of Covid-19mentioning
confidence: 99%
“…Other complaints include respiratory impairment, especially in patients with a severe COVID-19 course, and muscle or limb pain [5]. These symptoms post-COVID-19 decrease in frequency over months after the acute phase of infection [6], but how long they may persist, and whether they correlate with specific immunity, is unclear up to now.…”
Section: Introductionmentioning
confidence: 99%